Integration of Energy Quality and Financial Feasibility in the Production of Oil Palm Frond Chips and Pellets - Yogi Alamsah; Widayat Widayat; Sri Widodo Agung Suedy (Jurnal IPTEK Bagi Masyarakat, 2026)
Indonesia, as the world’s largest palm oil producer, generates significant quantities of oil palm frond (OPF) biomass that remain underutilized. This study evaluates the technical characteristics and economic feasibility of converting OPF into energy products in the form of chips and pellets. Laboratory analyses including proximate, ultimate, and calorific value tests were conducted to assess fuel quality, followed by a techno-economic evaluation using a 15-year investment horizon and an 11% discount rate. Results show that pelletization improves fuel properties, particularly by reducing moisture content and increasing calorific value under actual conditions. The higher heating value (HHV) of pellets reached 3,962 kcal/kg under air-dry conditions, compared to 1,746 kcal/kg for chips. On a dry ash-free basis, the calorific values of both products were comparable, indicating that moisture content significantly influences actual energy performance. Economic analysis indicates that pellet production under coal price equivalence schemes does not achieve attractive financial returns, with internal rates of return (IRR) below the discount rate and payback periods exceeding project lifetime. Sensitivity analysis suggests that a selling price of Rp1,000,000 per ton or a calorific value above 5,300 kcal/kg is required to reach financial feasibility. In contrast, chip production with low calorific value is economically unviable; however, improving chip quality to 4,060 kcal/kg results in a financially feasible scenario, achieving an IRR of 32.3% and payback within four years. The findings highlight that product form, energy quality, and market pricing mechanisms critically determine the viability of OPF-based bioenergy development.